Gallery Walk sebagai Strategi Penguatan Kemampuan Berpikir Kreatif dalam Pembelajaran Ilmu Pengetahuan Sosial - Revi Dahlianti (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to improve students’ creative thinking skills through the implementation of the gallery walk method in Social Studies learning for fourth-grade students at SDN 015 Gunung Bungsu. The method used is Classroom Action Research CAR, conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The results show a significant improvement from the first cycle to the second cycle. Student participation increased from 60% to 85%, while the average creative thinking ability rose from 50% to 77.5%. This improvement was observed across all indicators of creative thinking, namely fluency, flexibility, originality, and elaboration. Through this method, students became more active in discussions, more confident in expressing their ideas, and more capable of generating diverse and innovative ideas. Therefore, the gallery walk method is proven to be effective in creating an interactive, enjoyable, and meaningful learning environment for students in the classroom. This study also provides important implications for teachers in selecting appropriate and innovative learning strategies